Stakeholder Analysis in Community Based Mangrove Management: Case of Forest Management Unit in Region 3 of Aceh Province - OK Hasnanda; Bramasto Nugroho; Hariadi Kartodihardjo; Nyoto Santoso (Jurnal Manajemen Hutan Tropika, 2018)
Mangrove under the management of Forest Management Unit (KPH) region 3 of Aceh Province is a forest area located in the eastern coastal area of Aceh Province and has great functions and benefits for the community. To find out how big and how many the stakeholders involved in mangrove management was, an analysis to identify and to map how great the interest-power, and ability to interact in the network was carried out. Stakeholders were identified from a selected interview with snowball sampling method. How stakeholders interact in a network describes the relationship among stakeholders and interacts with one another. The results showed that there were 26 stakeholders. With stakeholder mapping, they will ensure their position on the grid can be seen how much power they have and how much interest they have in it. Some actors such as Pusong Kapal Village community, Pusong Telaga Tujoh Village community, community forest, the village head, and community leaders have indicated how to manage through support mechanisms, and foster aspirations when formulating and designing stronger strategies. Thus the FMU can build and maintain long-term relationships that involve patterns of interaction especially with stakeholders who have a significant influence on the network.